Aqueous extract of Amydrium sinense (Engl.) H. Li alleviates hepatic fibrosis by suppressing hepatic stellate cell activation through inhibiting Stat3 signaling - Li, Jingyan; Wu, Bingmin; Zeng, Lishan; Lin, Ying; Chen, Qiuhe; Wang, Haixia; An, Lin; Zhang, Jiajun; Chen, Siyan; Huang, Junying; Zhan, Ruoting; Zhang, Guifang (Frontiers in Pharmacology, 2023)
Background: The present study aimed to investigate the protective effect of the water extract of Amydrium sinense (Engl.) H. Li (ASWE) against hepatic fibrosis (HF) and clarify the underlying mechanism. Methods: The chemical components of ASWE were analysed by a Q-Orbitrap high-resolution mass spectrometer. In our study, an in vivo HF mouse model was established via an intraperitoneal injection of olive oil containing 20% CCl4. In vitro experiments were conducted using a hepatic stellate cell line (HSC-T6) and RAW 264.7 cell line. A CCK-8 assay was performed to assess the cell viability of HSC-T6 and RAW264.7 cells treated with ASWE. Immunofluorescence staining was used to examine the intracellular localization of signal transducer and activator of transcription 3 (Stat3). Stat3 was overexpressed to analyse the role of Stat3 in the effect of ASWE on HF. Results: Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses showed that candidate targets of ASWE, associated with protective effects against HF, were related to inflammation response. ASWE ameliorated CCl4-induced liver pathological damage and reduced the liver index and alanine transaminase (ALT) and aspartate transaminase (AST) levels. ASWE also decreased the serum levels of collagen Ⅰ (Col Ⅰ) and hydroxyproline (Hyp) in CCl4-treated mice. In addition, the expression of fibrosis markers, including α-SMA protein and Acta2, Col1a1, and Col3a1 mRNA, was downregulated by ASWE treatment in vivo. The expression of these fibrosis markers was also decreased by treatment with ASWE in HSC-T6 cells. Moreover, ASWE decreased the expression of inflammatory markers, including the Tnf-α, Il6 and Il1β, in RAW264.7 cells. ASWE decreased the phosphorylation of Stat3 and total Stat3 expression and reduced the mRNA expression of the Stat3 gene in vivo and in vitro. ASWE also inhibited the nuclear shuttling of Stat3. Overexpression of Stat3 weakened the therapeutic effect of ASWE and accelerated the progression of HF. Conclusion: The results show that ASWE protects against CCl4-induced liver injury by suppressing fibrosis, inflammation, HSC activation and the Stat3 signaling pathway, which might lead to a new approach for preventing HF.